Analysis and perception of flipped classroom teaching method among first year medical students - Jaysheela Bagi; Nirmala Anand; Vijaya S. Dandannavar; Saloni Manglik (Al Ameen Medical College, 2024)
Introduction: Flipped Classroom (FC) method is a new approach in which there is a switch between the work done in class and work done as homework. Background: Previous studies have had variable results. Some conclude neither an improvement nor degradation in students' performance, while others agree that the Flipped Classroom teaching model has value over traditional teaching styles. Objectives: To assess the effectiveness of the FC learning module on phase I medical students. Methods: There were mixed methods used in this study. For the students to compare the teaching methods, first a didactic lecture class was conducted followed by a more interactive flipped classroom for the interested students. After the classes, two questionnaires were given to them. One to receive their feedback on the teaching model, and one to assess the difference in performance between traditional and Flipped Classroom teaching models. Results: The test done to assess performance proved that the FC model was more effective as a teaching method. A high percentage of students also provided feedback in support of the FC model as compared to the traditional teaching method. Conclusion: The results of this study provide conclusive evidence of the Flipped Classroom teaching model being more effective for the understanding of concepts as well as the performance of phase I MBBS students. It is also a better method as per the students as understood from the feedback form.